Daily rhythm of glutathione peroxidase activity, lipid peroxidation and glutathione levels in tissues of pinealectomized rats - Baydas, G; Gursu, MF; Yilmaz, S; Canpolat, S; Yasar, A; Cikim, G; Canatan, H (Elsevier Sci Ireland Ltd, 2002)
Melatonin is a component of the antioxidant defense system since it has radical scavenging and antioxidant activities. In the present study, we aimed to investigate the endogenous rhythm of antioxidant enzyme glutathione peroxidase (GSH-Px) activity, oxidized glutathione (GSSG) and lipid peroxidation levels in tissues of pinealectomized rats (PINX). Rats were sacrificed by decapitation at 4 h intervals. GSH-Px activity, GSSG and lipid peroxidation levels showed a daily rhythm both in controls and in PINX rats. GSH-Px and GSSG exhibited the peak levels after the peak time of melatonin which was determined previously by other groups. Lipid peroxidation levels increased progressively during the night and started to decline before the GSH-Px peak time. These findings suggest that endogenous melatonin is involved in the night time increase of GSH-Px activity and GSSG levels and modulates the daily rhythm pattern of GSH-Px. In conclusion, pinealectomy which eliminates the melatonin rhythm has a supressor effect on GSH-Px activity levels. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: pinealectomy; melatonin; glutathione peroxidase; lipid peroxidation; daily rhythm